Perspectives of Management Accounting for Sustainable Business Practices - Oncioiu, Ionica (IGI Global, 2022)
In the 21st century, management accounting gains new dimensions, expanding its research area. Additionally, management of sustainable performance is one of the phenomena faced by the current business environment, and in particular management corporations. The focus of management on profitability remains the main objective of any company, but it must also take into account the sustainability of social, economic, and environmental aspects. Under these circumstances, managerial decisions must be adjusted and strongly substantiated considering the information required by internal and external stak.